Promoting Reflective Journal as an Approach to Enhancing EFL Students’ Writing Skills - effi wahyuningsih (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2019)
This study aims at improving the students’ writing skills through promoting reflective journal writing. This is a classroom action research. The data were gained through observation, questionnaire, interview, written testimonies, and writing tests. The research findings reveal that reflective journal writing promotes the students to get progress in their writing skills achieved through some indicators shown in each meeting. They cover the improvement of a) the mean score of each writing component affecting the increase of the mean score of the students' writing tests, b) the scoring category from "average" to "good", c) the number of students getting writing skills improvement, and d) the students' learning gain. In addition, the class of English (Beginner) which is especially focused on writing skills has been able to raise the students' motivation. It can be seen through their active participation, excitement, and positive response during the instructional process, and their interest in writing.